1999
DOI: 10.1002/(sici)1096-9837(199908)24:9<835::aid-esp15>3.0.co;2-g
|View full text |Cite
|
Sign up to set email alerts
|

A worldwide correlation for exponential bed particle size variation in subaerial aqueous flows

Abstract: The particle size of the bed sediments in or on many natural streams, alluvial fans, laboratory flumes, irrigation canals and mine waste deltas varies exponentially with distance along the stream. A plot of the available worldwide exponential bed particle size diminution coefficient data against stream length is presented which shows that all the data lie within a single narrow band extending over virtually the whole range of stream lengths and bed sediment particle sizes found on Earth. This correlation appli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
36
0

Year Published

1999
1999
2019
2019

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 68 publications
(37 citation statements)
references
References 42 publications
1
36
0
Order By: Relevance
“…The commonly observed downstream fining of grain size is typically treated as an exponential function (e.g. Morris and Williams, 1999), however, many field studies have found good agreement with a power law fining relation (e.g. Brush, 1961;Brierley and Hickin, 1985;Ohmori, 1991).…”
Section: Spatial Scaling From Reach To Longitudinal Profilesupporting
confidence: 91%
“…The commonly observed downstream fining of grain size is typically treated as an exponential function (e.g. Morris and Williams, 1999), however, many field studies have found good agreement with a power law fining relation (e.g. Brush, 1961;Brierley and Hickin, 1985;Ohmori, 1991).…”
Section: Spatial Scaling From Reach To Longitudinal Profilesupporting
confidence: 91%
“…It was applied empirically to numerous mine tailings beaches by Abadjiev [33,34] and Williams and Morris [7]. It has also been applied empirically to a large number of subaerial aqueous flows of all kinds [35].…”
Section: Mine Waste Beach Profiles and Flow Resistancementioning
confidence: 99%
“…Morris and Williams [32,35] also compiled independent data from more than one hundred natural streams, canals, laboratory flumes (mine tailings, sand, and gravel), tailings beaches, and coal co-disposal beaches (Fig. 13) that enable b to be evaluated.…”
Section: Ph Morrismentioning
confidence: 99%
See 1 more Smart Citation
“…Resistant rock units are generally associated with narrower valleys that confine floods, resulting in higher flood peaks and greater unit stream power (Baker and Costa, 1987;Magilligan, 1992). Differential rates and styles of weathering not only dictate the initial size (McPherson, 1971) of detached particles, but also the downstream rate of particle size reduction (Kodama, 1994;Morris and Williams, 1999;MoussaviHarami et al, 2004), thereby indirectly influencing the spatial distribution of sediment.…”
Section: Introductionmentioning
confidence: 99%